2002
DOI: 10.1163/156856802320401900
|View full text |Cite
|
Sign up to set email alerts
|

The stereoscopic anisotropy affects manual pointing

Abstract: Although binocular disparity can in principle provide absolute depth information, perceived stereoscopic depth depends on the relative disparities between points and their spatial arrangement. An example of this is the stereoscopic anisotropy--observers typically perceive less depth for stereoscopic surfaces when depth varies in the horizontal direction than in the vertical direction. We investigated whether this anisotropy also affects manual pointing. Participants were presented with stereograms depicting su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In line with previous studies on the association between victim sensitivity and depressive symptoms in non-clinical samples or personality traits related to depression (6,42,43), the present study found that patients with MDD had higher sensitivity to injustice as a victim. Particularly, this hypersensitivity can be found in a group of first episodic, drug-naïve patients with MDD, suggesting that the increased victim sensitivity was free from the confounding effect of chronic illness or antipsychotic drugs and could be observed even in the early stage of depression.…”
Section: Hypersensitivity To Injustice As a Victimsupporting
confidence: 92%
“…In line with previous studies on the association between victim sensitivity and depressive symptoms in non-clinical samples or personality traits related to depression (6,42,43), the present study found that patients with MDD had higher sensitivity to injustice as a victim. Particularly, this hypersensitivity can be found in a group of first episodic, drug-naïve patients with MDD, suggesting that the increased victim sensitivity was free from the confounding effect of chronic illness or antipsychotic drugs and could be observed even in the early stage of depression.…”
Section: Hypersensitivity To Injustice As a Victimsupporting
confidence: 92%
“…Such reduced slopes have also been obtained in past research. Both van Ee (2001; see the left panel of his Figure 4) and Bradshaw, Hibbard, van der Willigen, Watt, and Simpson (2002;see their Figure 4) found that the rate of increase in perceived slant (relative to increases in simulated slant) was considerably less than 1.0. Our stereoscopic results are especially close to those in Bradshaw et al (see their Figures 4A and 4C).…”
Section: Discussionmentioning
confidence: 93%